2020
DOI: 10.21873/anticanres.14085
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Analogues of Propanediamine Series Inhibit Prostate Tumor Cell Growth and Activate the Polyamine Catabolic Pathway

Abstract: Background/Aim. Polyamines are important for the growth of eukaryotic cells. At high levels, they promote proliferation, invasion and migration of tumour cells. Polyamine metabolism is an important new target for anticancer therapy. Some polyamine analogues can have an inhibitory effect on tumour cells. The aim of this study was to explore the potential of certain butylated derivatives of propanediamine for prostate cancer chemotherapy. Materials and Methods. Human prostate cancer cells, LNCaP, were used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The products of PA catabolism (mainly reactive oxygen species (ROS), such as hydrogen peroxide and acrolein) are capable of inducing cell death via apoptosis [25,26,32,33]. Apoptosis was the type of cell death in HepG2 cells when 4e was coincubated with Spd/Spm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The products of PA catabolism (mainly reactive oxygen species (ROS), such as hydrogen peroxide and acrolein) are capable of inducing cell death via apoptosis [25,26,32,33]. Apoptosis was the type of cell death in HepG2 cells when 4e was coincubated with Spd/Spm.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of these enzymes resulted in tumor sensitization to anticancer therapy [17,18] or in a decrease in tumor aggressiveness [19]. The degradation pathway of PAs includes different di-and polyamine oxidases [2,3] that are often reduced in cancer tissues [20,21], while the catabolic products of PA oxidation are able to induce apoptosis in normal and tumor cells [22][23][24][25]. Thus, activation of the PA catabolic pathway, primarily through a direct interaction with PA oxidases, may be a promising strategy for cancer therapy [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Each lobe has an iron-binding centre. The tertiary structures of apo-lactoferrin (iron-free lactoferrin) and iron-binding lactoferrin differ [4,6,7,8,9,10,13]. For example, it is found that Fе 3+ binding plays an essential role in implementing the antioxidant and bacteriostatic function of lactoferrin.…”
Section: R E L E V a N C Ementioning
confidence: 99%
“…1). They are essential for cell growth, cell proliferation and differentiation (8,9), and have the ability to coordinate the process of cell apoptosis (9)(10)(11)(12)(13). The contents of the PAs spermine (Spm) and spermidine (Spd) in the seminal plasma are significantly higher than in any other biological fluid, which highlights the importance of these low molecular weight organic polycations for human reproductive function, especially in men (10,14).…”
Section: Introductionmentioning
confidence: 99%